The clinical-epidemiological characteristics of tick-borne rikkettsiosis in Baikal regions - K. A. Aitov; V. I. Zlobin; I. V. Malov; B. A. Borisov (Бюллетень сибирской медицины)
The clinical-epidemiological characteristics of tick-borne rikkettsiosis in Eastern Siberia is given. Prevalence of the disease in villages is higher comparing towns. The carrier of infection is Dermacentor ticks which live in steppe and forest-steppe zones closer to dwellings. Medium course of disease is prevailed and the prognosis of disease is good.